Effect of added silicon carbide nanowires and carbon nanotubes on mechanical properties of 0-3 natural rubber composites - Khantichai Janyakunmongkol (2018)
© 2016 The Japan Society of Applied Physics. In this work, the mechanical properties of 0-3 nanocomposite materials containing silicon carbide nanowires (SiCNWs), carbon nanotubes (CNTs), and natural rubber were studied. The SiCNWs and CNTs were used as reinforcement fiber whereas natural rubber was used as the matrix phase. The chemical vapor depositions (CVD) was used for synthesizing the nanowire and nanotube phases. The volume fraction of reinforcement was varied from 0 to 10%. The nanophases were mixed in the natural rubber matrix and molded by the hand lay-up technique. The mechanical properties of the samples were examined and compared with those of neat natural rubber. From the results, it was found that the hardness and density of the samples increased with the quantities of nanophases. The nanocomposites with a volume fraction of 10% exhibited maximum hardness (50.5 SHORE A). The maximum tensile strength and extent of elongation at break of the samples were obtained from the 4% volume fraction sample, which were 16.13MPa and 1,540%, respectively.